Preliminary DRIS norms for sugarcane developed from a low number of samples - Galíndez, Aymara Aracelis Sánchez; Cruz, Jeglay Giralí; Zérega, Luis; Rodríguez, Orlando Antonio Rodríguez; Oliveira, Sebastiao Alberto de; Pérez, Vianel de Jesus Rodríguez (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the feasibility of developing preliminary DRIS norms from a low number of leaf samples of sugarcane grown on a homogeneous soil series, as an alternative to diagnose the nutritional equilibrium of the crop. The research was carried out in Central Azucarero Portuguesa sugarcane mill, Portuguesa state, Venezuela. From May to July 2004, composite leaf samples from 32 different sugarcane-producing areas were collected and analyzed for nitrogen, phosphorus, calcium, magnesium, boron, copper, iron, manganese, zinc and sodium. All the sampled areas were from the Agua Blanca series (Aquic Haplustoll) and had a high historical record of stalk productivity. A normal data bank was obtained, which provided confidence for the development of preliminary DRIS norms. These norms showed coincidences and differences with previously reported ones in the literature. The content of sodium as a diagnostic norm was reported. A low number of leaf samples are sufficient to develop norm data banks and preliminary DRIS norms for nutritional diagnosis of sugarcane.